The Association of Service Quality with Patient Satisfaction and Loyalty: a Cross-Sectional Path Analysis in a Pediatric Outpatient Clinic - Arib Balma, Hammam; Rochani Mulyani, Sri; Rulia, Rulia; Nugroho, Taufan; Paramarta, Vip (Journal of Economics and Business UBS, 2025)
The quality of service is consistently related to patient satisfaction and loyalty in children's health services, where clinical competence must be balanced with the delivery of responsive, patient-centered services. Examining the relationship between service quality and patient loyalty through patient satisfaction at the Children's Polyclinic of Ananda Lubuklinggau Mother and Child Hospital (RSIA). This study is a cross-sectional survey of 100 patients/parents of patients (purposive sampling; May–June 2025) using validated instruments for service quality (based on SERVQUAL), patient satisfaction (based on PSQ derivatives), and patient loyalty (6 statements). Descriptive analysis and path analysis were carried out using SPSS version 29. All constructs were rated in the "good" category: quality of service (M = 3.60), satisfaction (M = 3.43), and loyalty (M = 3.60). Quality of service was significantly related to satisfaction (β = 0.619; p < 0.001; R² = 0.383) and loyalty (β = 0.599; p < 0.001), while satisfaction was positively correlated with loyalty (β = 0.317; p < 0.001), with the loyalty model explaining 69.5% of the variance (R² = 0.695). The mediation analysis showed that satisfaction partially mediated the relationship between service quality and loyalty, with a standardized indirect effect of 0.196 and a standardized total influence of 0.795, suggesting that service quality had the strongest relationship with loyalty. Improved responsiveness (waiting time and punctuality of doctors), waiting room comfort, availability of real-time service information, and doctor-patient communication are related to increased satisfaction and can strengthen patient loyalty. Given the cross-sectional design of the study, longitudinal studies are needed to confirm the causal relationship.